Q: How do you solve step by step cube of binomial?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(8m+6)

that;s so simple . try it

Binomial Expansion makes it easier to solve an equation. It brings an equation of something raised to a power down to a solveable equation without parentheses.

The cube of a binomial is the cube of two terms separated by an addition or subtraction sign, such as (2a + 3b) or (ab - cd).For example, (2x - 5y)3 = 8x3 - 40x2y + 50xy2 - 20x2y + 100xy2 - 125y3.The detailed method of expanding this binomial is : (2x - 5y)3 = (2x - 5y)(2x - 5y)(2x - 5y) = (4x2 - 20xy + 25y2)(2x - 5y) = 8x3 - 40x2y + 50xy2 - 20x2y + 100xy2 - 125y3

To solve something you need an equation (or inequality). An equation comprises two expressions with an equality sign between them. Here, there is only one expression: the "square of binomial". So, you cannot solve it.You expand the expression as follows:(ax + b)^2 = a^2x^2 + 2abx + b^2

Related questions

Consider a binomial (a+b). The cube of the binomial is given as =(a+b)3 =a3 + 3a2b + 3ab2 + b3.

In Step 1 and the final step to solve the 1x1, you use a algorithm, that algorithm is U Ui.

99x99x99

To calculate the cube of a binomial, you can multiply the binomial with itself first (to get the square), then multiply the square with the original binomial (to get the cube). Since cubing a binomial is quite common, you can also use the formula: (a+b)3 = a3 + 3a2b + 3ab2 + b3 ... replacing "a" and "b" by the parts of your binomial, and doing the calculations (raising to the third power, for example).

step 1 the daisy

jb+++u

(8m+6)

that;s so simple . try it

STEPS : FIRST TERM = the cube of the first term SECOND TERM=three times the product of the squareof first term and second term THIRD TERM=three times the product of first term and square of second term FOURTH TERM=THE CUBE OF THE LAST TERM ..

STEPS : FIRST TERM = the cube of the first term SECOND TERM=three times the product of the squareof first term and second term THIRD TERM=three times the product of first term and square of second term FOURTH TERM=THE CUBE OF THE LAST TERM ..

STEPS : FIRST TERM = the cube of the first term SECOND TERM=three times the product of the squareof first term and second term THIRD TERM=three times the product of first term and square of second term FOURTH TERM=THE CUBE OF THE LAST TERM ..

Finding the cube root of 3 would not have helped.